La comunicación para el desarrollo y Unicef - Crego Hernández, Elena (Revista Española de Desarrollo y Cooperación, 2023)
The article displays some of the main initiatives that The United Nations Children’s Fund – (UNICEF) has undertaken in the field of communication. This organization has been using a wide range of tools since 1970’s to promote the children’s rights, their survival, development and protection from a communicative perspective.